Odpowiedzi

2010-02-11T14:34:54+01:00
A=0,1 i b= -10
(2ab+b)-b(a-2ab+a²)=
(2*0,1*(-10)-10)+10(0,1+2*0,1*10+0,1²)=
(-2-10)+10(0,1+2+0,01)=
-12+10(2,11)=
-12+21,1=9,1
2010-02-11T14:42:30+01:00
A(2ab+b)-b(a-2ab+a²) dla a=0,1 i b= -10
0,1(2*0,1*-10+-10)+10(0,1-2*0,1*-10+0,1²)=0,2*0,01*-1*-1+1*-20*1*-100*0,1=2200
Najlepsza Odpowiedź!
2010-02-11T15:14:06+01:00
A(2ab+b)-b(a-2ab+a2)= 0.1( 2* 0.1 * (-10))- 10 (0.1 - 2 * 0.1*(-10)) +0.12(ta dwójka oznacza do potegi 2)= 0.1*2- 10(0.1+2+0.01)= 0.2- (10*2.11)=0.2- 21.1=-20.9